To improve the future profit expectations of the Nissan stamping plant - Elliott, Paul Leslie (Department of Mechanical Engineering, 2016)
The process of thought applied to establish a thesis topic has been one of non-acceptance of the situations on face value. As such the future profitability of the Nissan Stamping Plant has been considered. A mental model has been established in the authors mind that a definite problem exists within this area. This has led to the formulation of a framework that can be used to handle the problem of low profits that will eventually lead to the closure of the operation. Status-Quo has remained within the operations for almost 25 years, but now changes in Government Legislation pose threats. This leads to the question of how can the profits be improved. The framework was built around a philosophy of continual search for the truth. The scientific method has been applied to understand the theories of a single or double loop response whilst proceeding through the Plan, Do, Check, and Action cycle.